AKTIVITAS BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SOSIOLOGI KELAS XI IPS SMAN 3 LENGAYANG KABUPATEN PESISIR SELATAN - Putri, Nesi Eka; Zafri, Zafri; Erningsih, Erningsih (Pendidikan Sosiologi, 2013)
Nesi Eka Putri (09070022), Learning Activities Students Lesson In Sociology Class XI IPS SMAN 3 Lengayang South Coastal District. Thesis. Sociology of Education Studies Program (STKIP) PGRI West Sumatra, Padang, 2013The research was motivated by the low activity of learners in sociology lesson. The low activity of learners is shown from the students are not serious in learning, while the teacher explains lessons chide and creative learners in improving learning less look of the tasks performed by the students did not do well. This study aimed to describe the activities of learners in the learning process sociology class XI IPS SMAN 3 Lengayang South Coastal District.Type of research is classified by the type of descriptive qualitative research. The research object is the class XI students of SMAN 3 Lengayang IPS2 South Coastal District by the number of students by 32 people.The tool used for this study is a list that contains the results of observation checklists and learning activities of learners are processed using the formula percentage (%).These results indicate that the percentage of learners learning activities in class XI IPS2 SMAN 3 Lengayang listen to an explanation for the activity with the percentage of 53.26% of teachers, students listen to a friends question with a percentage of 27.41%, the students listened to a friend reply percentage of 28.10%, students read the book before the learning process starts with a percentage of 3.89%, students read notes/ summary of lessons with a percentage of 5.18%, subject matter with students noting the percentage of 38.53%, accounting for the bulk of students/ incomplete material that teaches about the percentage 24.88%, the student asked the teacher if students do not understand the material being taught with a percentage of 1.91%, the students asked the friend if students do not understand the material being taught teachers with a percentage of 5.09%, students answer questions from teachers and friends during the learning process takes place with a percentage of 1.91%, students only have to answer questions from the teacher during the learning process takes place with the percentage of 10.2%, of students working on a given task well with the percentage of 34.36 % of teachers, students working on the task only partially/ not complete with the percentage of 36.58%